Platelet-activating factor modulates apoptotic gene expression in developing sea urchin embryos - Saha, Shohom; Cho, Aaron; Smith, Caroline; Roudebush, William E.; Chosed, Renee J. (Frontiers in Cell and Developmental Biology, 2026)
Examining gene expression patterns during early embryonic development is essential for understanding genetic disorders and fertility. The accessibility, cost-effectiveness, and reproducibility of sea urchin embryos have offered an effective model for studying how gene expression is regulated in early embryogenesis under the influence of specific growth factors. However, regulation of apoptotic gene expression by growth factors, such as Platelet-Activating Factor (PAF), during early embryogenesis remains unexamined. This study investigated the role of PAF during the first 4 hours post-fertilization in sea urchin (Lytechinus variegatus) embryos. Using quantitative real-time polymerase chain reaction (qRT-PCR), we analyzed expression patterns of apoptosis-promoting genes (CASP3, CASP7 and CASP8) and apoptosis-inhibiting genes (BCL2A1, NFKBIA, NFKBIZ) in PAF-treated and untreated embryos collected at 20-min intervals for up to 240 min of development post-fertilization. This study revealed that PAF increases the expression of both pro-apoptotic caspase genes across all time points and anti-apoptotic genes in a biphasic manner. Our results demonstrate complex regulatory mechanisms that maintain the function of apoptotic machinery while preventing excessive cell death during critical early developmental stages.